PENGARUH LAMA PEMBAKARAN DAN JENIS BAHAN BAKAR TERHADAP KUALITAS KIMIA, FISIK, SENSORIS DAN KADAR BENZO(A)PIREN SATE DAGING KAMBING - , BAYU ETTI TRI ADIYASTITI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study was conducted to determine the influence of grilling duration and fuel type on quality of chemical, physical, sensory and levels of benzo(a)pyrene of goat meat satay. as the first preparation, the meat was marinated with herbs, skewered by bamboo and grilled according to the treatments. The grilling duration treatments were 3, 5 and 7 minutes by charcoal and gas. The parameter of this study were The quality of chemical, physical, sensory and levels of benzo(a)pyrene. The quality data were statistically analyzed used a complete random factorial design of 3x2 if there were differences, the further analysis would be conducted by Duncanâs New Multiple Range Test. Sensory quality data were analyzed by Kruskal-Wallis non-parametric analysis method and levels of benzo(a)pyrene would be explained descriptively. Statistical analysis results showed that the grilling duration had a significant affected on the water, protein and ash content of goat meat satay. The fuel types were not significantly affected to the water, protein and ash content. Statistical analysis results showed that grilling duration and fuel type did not have significantly affected to the fat content of goat meat satay. Statistical test results indicated that the grilling process by different grilling duration and fuel type had no significantly affected to the value of pH in goat meat satay. The grilling duration had significant affected to the value of tenderness. Statistical analysis results showed that the grilling duration significantly influenced the meat's color, taste, juiciness and acceptance, but it did not significantly affect the meat's smell and texture. Fuel type did not significantly determine the sensory quality. The levels of benzo(a)pyrene meat goat satay of charcoal fuel with 3, 5 and 7 minutes grilling duration in sequence were 2.55 ppb